Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.2465/jmps.170613b
|View full text |Cite
|
Sign up to set email alerts
|

Late Cretaceous CHIME monazite ages of Sanbagawa metamorphic rocks from Nushima, Southwest Japan

Abstract: The Sanbagawa metamorphic rocks of epidote-amphibolite facies are extensively exposed in Nushima at the southern end of the Hyogo Prefecture, Japan. Chemical U-Th-total Pb isochron method (CHIME) ages were determined for monazite grains from the Sanbagawa metamorphic rocks. CHIME monazite ages are 92.3 ± 3.2 and 90.3 ± 4.7 Ma for two chlorite-rich rocks collected from the reaction zone between pelitic schists and serpentinites. The monazite grains occur as isolated phases or aggregates with rutile/ilmenite in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…andItaya and Tsujimori (2015) reported 40 Ar/ 39 Ar amphibole and phengite ages of 87-95 Ma and K-Ar phengite ages of 84-89 Ma from the Seba eclogites and related metapelites, respectively. Similar K-Ar phengite and paragonite ages of 78-80 Ma were also described from the Western Iratsu eclogites(Itaya & Tsujimori, 2015) Suzuki et al (2018). discussed the relationships between the U-Pb, Sm-Nd, and Lu-Hf ages and equilibrium conditions of the Sanbagawa eclogites, and suggested a possibility that the quartz eclogites and other lithologies in the eclogite-unit formed at different depths and periods of the Sanbagawa subduction, which could have continued for more than 20-30 Ma(Figure 2).…”
supporting
confidence: 69%
See 2 more Smart Citations
“…andItaya and Tsujimori (2015) reported 40 Ar/ 39 Ar amphibole and phengite ages of 87-95 Ma and K-Ar phengite ages of 84-89 Ma from the Seba eclogites and related metapelites, respectively. Similar K-Ar phengite and paragonite ages of 78-80 Ma were also described from the Western Iratsu eclogites(Itaya & Tsujimori, 2015) Suzuki et al (2018). discussed the relationships between the U-Pb, Sm-Nd, and Lu-Hf ages and equilibrium conditions of the Sanbagawa eclogites, and suggested a possibility that the quartz eclogites and other lithologies in the eclogite-unit formed at different depths and periods of the Sanbagawa subduction, which could have continued for more than 20-30 Ma(Figure 2).…”
supporting
confidence: 69%
“…Schematic diagram showing the pressure–temperature–time (P–T–t) paths of the eclogite and non‐eclogite units of the Sanbagawa belt (modified from Figure b of Suzuki, Enami, Maekawa, Kato, and Ueno ()). A09, Aoki et al (); I11, Itaya, Tsujimori, and Liou (); O04, Okamoto et al (); W09, Wallis et al (); S18, Suzuki et al ()…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Suzuki et al. () suggested that different peak eclogite facies metamorphic ages reported by Okamoto et al. () and Wallis et al.…”
Section: Geological Backgroundmentioning
confidence: 93%
“…In comparison with the U-Pb zircon ages reported from previous geochronological studies, they interpreted the main stage of the Sanbagawa prograde metamorphism, up to the epidote-amphibolite facies, at 92-81 Ma. In addition, Suzuki et al (2018) suggested that different peak eclogite facies metamorphic ages reported by Okamoto et al (2004) and Wallis et al (2009) may reflect their formation at different depths and periods during a single Sanbagawa subduction episode (e.g., Endo et al, 2012).…”
Section: F I G U R E 1 (A) Metamorphic Zonationmentioning
confidence: 99%